Spatio-temporal assessment of the impacts of the trends in physical and biogeochemical parameters on the primary production of the Gulf of Guinea - Adeola M. Dahunsi; Tolulope S. Oyikeke; Mujeeb A. Abdulfatai; Lateef A. Afolabi (Heliyon, 2023)
This study applied ocean models data from Copernicus Marine Environment Monitoring Service (CMEMS) in assessing the impacts of the trends in key ocean parameters on the primary production of the Gulf of Guinea (GoG). Trend analyses, from 1993 to 2020, were done using linear regression and Mann-Kendall significance test methods to ascertain inter-annual and inter-seasonal variations and check the significance of the trends, respectively. Results affirm that temperature, salinity, nutrients, and oxygen play significant roles in the primary production of the GoG. Also, parameters such as temperature, salinity, chlorophyll-A, net primary production, phosphate, and dissolved oxygen have been experiencing increases between the study duration while silicate and nitrate have been declining in the GoG. However, there are regions and years with contrary values to the average trends. The varying level of significance of the trend showed that the impacts of the climate on the primary production of the GoG vary basin-wide.